Application of Distributed Optical Fibre Sensor for Strain and Temperature Monitoring within Continuous Flight Auger Columns. (January 2019) - Sienko, Rafal; Bednarski, Lukasz; Kanty, Piotr; Howiacki, Tomasz
Abstract: Distributed optical fibre technology provides new possibilities in structural health monitoring in comparison with traditional spot measurements, because it allows to measure selected physical quantities continuously over structural member length. The spatial resolution can start from as fine as 5 mm when using advanced optical reflectometers based on the principle of Rayleigh scattering. The quality of information obtained about structural condition is especially important for geotechnical applications because there are many uncertainties regarding the theoretical model describing cooperation between the foundations and the substrate as well as including the values of physical parameters. Moreover, the geometry of structural members (e.g. the diameter of the column) can be very different from design assumptions and vary along the depth depending on technology of execution. In presented case study the analysis of continuous flight auger (CFA) column was described based on the strain and temperature measurements carried out continuously over the length of 12 m. The measurements were done during the load tests, but also in the early-age concrete, when thermal-shrinkage strains appeared. The way of installation and exemplary results were presented as well as data interpretation was described and discussed hereafter.